Impacts of Access to and Use of Electricity on Households’ Economic Status in Selected Informal Settlement Areas of Woreda 12, Yeka Sub city, Addis Ababa, Ethiopia - Nibretu Kebede; Degefa Tolossa; Tamirat Tefera (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2022)
At present, although electricity is essential for all human beings, it is not equally accessible to all. This paper analyzed the impact of access to and use of electricity on the economic status of informal settlements in Addis Ababa based on 450 households drawn from three sites of Woreda 12, Yeka Sub-City. The respondents were selected using proportional random sampling method and data were analyzed using descriptive statistics and Endogenous Switching Regression (ESR) models. The study revealed that non-users of electricity shifted more family labor to domestic activities, baked Injera less frequently per week, owned small number of home-based businesses, and used less alternative fuels than electric- users. However, due to lack of reliable energy supply and food consumption behaviors (FCBs), households do not completely rely on a single energy source. These situations could draw the attention of the government to provide reliable electric supply to non-users of electricity living sporadically mixed with electric-users, close to electric facilities and change households' energy consumption behaviors using alternative energy sources with the concept of energy stacking.